An Investigation of the Psychometric Properties of the Strong Brand Questionnaire in Sport - Mona Rezaei; Fatemeh Kiani (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Building strong brands has become a marketing priority for many organizations. The brand is an important criterion for the marketing situation. Power of brand effects on customer maintenance, financial benefit, brand broadening, and rivalry advantages... and is a concept, which was made by the consumer. The presumption is that building a strong brand yields a number of marketing advantages. Objectives. The purpose of this study was to investigate the psychometric properties of the strong brand questionnaire among the consumers of sports products. Methods. The questionnaires were administrated to 340 customers. The psychometric properties were determined based on the appropriate statistical methods. Results. The results obtained from the factor analysis via varimax rotation indicated the five factors of the strong brand scale, The relationship between 4 scales on the first scale were more than 0.49, 4 scales on the second scale were more than 0.46, and 4 on the third scale were more than 0.57, 5 scales on the fourth scale were more than 0.33, and 6 scales on the fifth scale were more than 0.35, which later fitted the confirmatory factor analysis. According to conformity indicators for brand strength, the first factor was brand development, the second factor was brand identity, and brand image, brand personality and brand equity respectively were the third to fifth factors. The reliability coefficients of the internal consistency including Cronbach's alpha was satisfactory for elements and factors (0.859). Conclusion. According to the estimated psychometric properties, this instrument can be used by the researchers in order to assess the achievement goals orientations among the sports product's customer.